PENGARUH ADVERSITY QUOTIENT (AQ) TERHADAP KEMAMPUAN LITERASI STATISTIS SISWA - Arif Prasetyo, Muhammad; Hayati, Laila; Humaira Salsabila, Nilza; Turmuzi, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the effect of Adversity Quotient (AQ) on statistical literacy abilities of class VIII students of MTsN 1 Mataram in the academic year 2023/2024. The type of this study is quantitative research. The population of this study was 318 students of class VIII MTsN 1 Mataram in the academic year 2023/2024. The sample used in this study was 77 students selected by cluster random sampling technique. The instruments in this study used Adversity Quotient (AQ) questionnaire and statistical literacy skills test. The results showed that there is a significant effect of Adversity Quotient (AQ) on the statistical literacy abilities of class VIII students of MTsN 1 Mataram in the academic year 2023/2024 with an influence contribution of 50,9%. Suggestion for future researchers is to examine other factors that affect statistical literacy abilities, both internal and external factors.